I was trying to prove that $\sqrt[3] {2} ,\sqrt[3] {4}$ and $1$ are linearly independent using elementary knowledge of rational numbers. I also saw this which was in a way close to the question I was thinking about. But I could not come up with any proof using simple arguments. So if someone could give a simple proof, it would be great.

My try:

$a \sqrt[3] {2}+b\sqrt[3] {4}+c=0$ Then taking $c$ to the other side cubing on both sides we get $2a^3+4b^3+6ab(a+b)=-c^3$. I could not proceed further from here.

Apart from the above question i was also wondering how one would prove that $\sqrt{2},\sqrt{3},\sqrt{5},\sqrt{7},\sqrt{11},\sqrt{13}$ are linearly independent. Here assuming $a\sqrt{2}+b\sqrt{3}+c\sqrt{5}+...=0$ and solving seems to get complicated. So how does one solve problems of this type?

  • $\begingroup$ I didn't read the accept answer in the linked question, but it seems exactly what you want applied in a different case. $\endgroup$ – Git Gud Jun 10 '14 at 10:16
  • $\begingroup$ @GitGud yes i want a proof for a different case but I tries to use the same method like cubing but could not conclude anything $\endgroup$ – happymath Jun 10 '14 at 10:18
  • 3
    $\begingroup$ Your edit just changed the question entirely. If you have new questions, please ask them separately. $\endgroup$ – Shaun Jun 10 '14 at 10:29
  • 1
    $\begingroup$ I accept your apology. Please don't do it again :) $\endgroup$ – Shaun Jun 10 '14 at 11:11
  • 1
    $\begingroup$ You may want to check math.stackexchange.com/questions/30687/… $\endgroup$ – Macavity Jun 10 '14 at 11:12

Let $\alpha=\sqrt[3] {2}$ and suppose $a+b\alpha+c\alpha^2=0$ with $a,b,c\in \mathbb Z$, which we may assume coprime.

Then $a\alpha+b\alpha^2+2c=0$ and $a\alpha^2+2b+2c\alpha=0$.

This means that the matrix below is singular $$ \pmatrix{ a & b & c \\ 2c & a & b \\ 2b & 2c & a} $$ Its determinant must be zero: $$ a^3-6 a b c+2 b^3+4 c^3=0 $$ This implies that $a$ is even: $a=2A$. So $$ 4A^3-6 A b c+ b^3+2 c^3=0 $$

This implies that $b$ is even: $b=2B$. So $$ 2A^3-6 A B c+ 4B^3+ c^3=0 $$ This implies that $c$ is even. This contradicts they being coprime.

  • $\begingroup$ thanks for the awesome proof $\endgroup$ – happymath Jun 10 '14 at 13:06
  • 1
    $\begingroup$ Using $a$ and $\alpha$ makes this a bit confusing at first. $\endgroup$ – robjohn Dec 17 '15 at 7:51

Suppose $1,\sqrt[3]2,\sqrt[3]4$ are linearly dependant. This means that there is a nonzero polynomial $P \in \Bbb Q[X]$ of degree at most $2$ such that $P(\sqrt[3]2)=0$.

However, we know that $Q = X^3-2$ also satisfies $Q(\sqrt[3]2) = 0$. By taking the greatest common divisor of $P$ and $Q$, we obtain a strict divisor $R$ of $Q$ (because the degree of $R$ is less than the degree of $Q$).

By Eisenstein's criterion, $Q$ is irreducible, which contradicts the existence of $R$.

For your second question :

If you know about the quadratic reciprocity law and Dirichlet's theorem about primes in arithmetic progression, you can show that the family of $\sqrt p$ are linearly independant :

If a relation existed between the square roots of a family of primes $p_0, \ldots, p_n$, then you can express $\sqrt{p_0}$ in terms of all the others. Such a formula means that $X^2 - p$ has a root in $\Bbb Q[T_1,\ldots,T_n]/(T_1^2-p_i)\ldots(T_n^2-p_n)$. If we have a prime $q$ such that (1) $q$ doesn't divide any denominator in the coefficients of the root, and (2) $p_i$ has a square root mod $q$ for $1 \le i \le n$ but not for $i=0$, you get a contradiction by looking at the root modulo $q$.
But such a prime exists because by the quadratic reciprocity law, (2) is equivalent to a modular condition, and then Dirichlet's theorem shows that there are infinitely many primes satisfying it, so there is one that satisfy (1).

In fact this shows even more : the family of $\sqrt n$ with $n \in \Bbb Z$ and $n$ squarefree, is linearly independant.

  • 2
    $\begingroup$ Hmm.. let me remind that the question was, how to prove all this using only elementary knowledge about rationals. $\endgroup$ – Vladimir Jun 10 '14 at 11:46
  • $\begingroup$ @Vladimir I don't think the second question can be answered with only elementary knowledge about rationals. Of course, feel free to contradict me on this. $\endgroup$ – mercio Jun 10 '14 at 11:57
  • $\begingroup$ I absolutely agree. That is why I have answered only the first:) $\endgroup$ – Vladimir Jun 10 '14 at 11:58
  • $\begingroup$ @mercio thanks a lot for your answer $\endgroup$ – happymath Jun 10 '14 at 13:03

Here's a simpler proof.

Let $\alpha=\sqrt[3] {2}$ and suppose $a+b\alpha+c\alpha^2=0$ with $a,b,c\in \mathbb Z$.

Then $a\alpha+b\alpha^2+2c=0$.

Now $0=b(a+b\alpha+c\alpha^2)-c(a\alpha+b\alpha^2+2c)=(ab-2c^2)+(b^2-ac)\alpha$.

Since $\alpha$ is irrational, we must have $ab=2c^2$ and $ac=b^2$. This implies $ab^3=2ac^3$. Since $\alpha$ is irrational, we must have $a=0$ and so $b=0$ and $c=0$.


Consider $c_1\sqrt{2}+c_2\sqrt{3}+c_3\sqrt{5}=0$. Then $c_1\sqrt{2}+c_2\sqrt{3}=-c_3\sqrt{5}$. Squaring both sides we will have $2c_1^2+3c_2^2+2\sqrt{6}c_1c_2=5c_3^2$. If either $c_1$ or $c_2$ turns out to be $0$ then we will either have $c_2\sqrt{3}+c_3\sqrt{5}=0$ implying $3c_2^2=5c_3^2$ which gives $\left(\frac{c_2}{c_3}\right)^2=\frac{5}{3}$ which is not possible . Similarly for the case when $c_2$ is $0$. (It is obvious when both $c_1$ and $c_2$ are $0$.) Hence if $c_1$ and $c_2$ are both non-zero then $$-\sqrt{6}=\frac{2c_1^2+3c_2^2-5c_3^2}{2c_1c_2}.$$

Now observe that the R.H.S is a rational no but the L.H.S is not.

  • $\begingroup$ I apologise for having changed the question entirely. Please have a look at it. $\endgroup$ – happymath Jun 10 '14 at 10:38

First show that $1$ and $\sqrt[3]2$ are linearly independent. (This should be relatively easy.)

Then in order for $1$, $\sqrt[3]2$ and $\sqrt[3]4$ to be linearly dependent we must have $$\sqrt[3]{4}=a+b\sqrt[3]2$$ for some $a,b\in\mathbb Q$. (Since $\sqrt[3]{4}$ is a linear combination of $1$ and $\sqrt[3]2$.)

If we multiply the above equation by $\sqrt[3]2$, we get \begin{gather*} 4=a\sqrt[3]2+b\sqrt[3]4=a\sqrt[3]2+b(a+b\sqrt[3]2)=(a+b^2)\sqrt[3]2+ab\\ 4-ab=(a+b^2)\sqrt[3]2 \end{gather*} Since $1$ and $\sqrt[3]2$ are linearly independent, we get $4-ab=a+b^2=0$.

So we get \begin{align*} ab&=4\\ b^2&=-a \end{align*} which yields $b^2=-\frac4b$ and $b^3=-4$. This means that there is no rational solution.

(Notice that $ab=4$ implies $b\ne0$, hence we could divide the first equation by $b$ to get $a=\frac4b$.)


We argue by contradiction. Obviously, $a\ne0$ and $b\ne0$. Then $x=\sqrt[3]2$ is a root of the square equation with rational coefficients and hence can be represented in the form $$ x=A+\sqrt{B} \qquad\text{or}\qquad x=A-\sqrt B $$ with rational $A$ and $B\ge0$. In fact, $B>0$, otherwise $x$ would be rational. We have $$ 2=x^3=A^3\pm3A^2\sqrt B+3AB\pm B\sqrt B=A^3+3AB\pm(B+3A^2)\sqrt B $$ Since $B>0$, it follows that $B+3A^2\ne0$ and hence $\sqrt B$ is rational. Thus, so is $x$. Contradiction.

  • $\begingroup$ nice proof thanks a lot $\endgroup$ – happymath Jun 10 '14 at 13:07

The linear independence of the square roots, can be noted from these propositions.

  1. Suppose that some (1:) $a^n = \sum^{n-1}_{x=0} z_x a^x $. If $a$ were rational, then the reduced form is some $a=p/q$ where $\gcd(p,q)=1$. If we multiply the defining equation by $q^n$, then all the right-hand terms are miltiples of q, where the LHS is not, unless $q=1$. This means that equation 1 defines a set that is integer or irrational. We can call these numbers 'irrational integers' $\mathbb{Y}$.

  2. All of the roots of integers solve (1:), in the form that $a^n = z$ gives $a=\sqrt[n]{z}$.

  3. Every irrational integer divides some integer. (Proof: multiply (1:) by $1/a$, this gives an expression in a = $z_0 / a$.

  4. The linear independence of square roots $p$, $q$ derives directly from (2), in that the $\sqrt{pq}$ is itself an irrational integer, either in Z or Y. We let $e+f\sqrt{p}+g\sqrt{q}+h\sqrt{pq}=0$ and let $(e+h\sqrt{pq})^2=(f\sqrt{p}+g\sqrt{q})^2$ or $(e^2+h^2pq)+2eh\sqrt{pq} = pf^2+qg^2 + 2fg\sqrt{pq}$.

  5. Similarly, we assert that $e^2f^2 = qg^2h^2$ and $e^2g^2=pg^2h^2$, but we have demonstrated that this can not happen in the integers, so $\sqrt{pq}$ is linearly independent from $1,\ \sqrt{p}, \sqrt{q}$.

    1. If any two numbers $a,b,c,\dots$ in $a+b\sqrt{z_1}+c\sqrt{z_2}+\dots$ are non-zero, then the square contains a sqruare root term. Since some $n\sqrt{z_n}$, not in the above set, has a square with no square-root term, then $n\sqrt{z_n}=d\sqrt{z_d}$, exactly. But if $z_n$ is not co-square with any of the list, then its square root can not be in the named span.

This implies that all of the square roots of square-free numbers are linearly independent, viz 1, 2, 3, 5, 6, 7, 10, 11, 13, 14, 15, 17, 19, 21, 22, 23, 26, 29, 30, &c.

Note that this proof generalises to all powers. A root number is not a member of a span of numbers, unless it is an integer multiple of exactly one member.

  • $\begingroup$ here in the answer are $z_x$ integers? and if i am not wrong you are talking about algebraic integers right? $\endgroup$ – happymath Dec 18 '15 at 11:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.